Short-term outcomes of cochlear implantation for single-sided deafness compared to bone conduction devices and contralateral routing of sound hearing aids—Results of a Randomised controlled trial (CINGLE-trial) - Jeroen P. M. Peters; Jan A. A. van Heteren; Anne W. Wendrich; Gijsbert A. van Zanten; Wilko Grolman; Robert J. Stokroos; A.L. Smit (2021)
Single-sided deafness (SSD) leads to difficulties with speech perception in noise, sound localisation, and sometimes tinnitus. Current treatments (Contralateral Routing of Sound hearing aids (CROS) and Bone Conduction Devices (BCD)) do not sufficiently overcome these problems. Cochlear implants (CIs) may help. Our aim was to evaluate these treatments in a Randomised Controlled Trial (RCT). Adult SSD patients were randomised using a web-based randomisation tool into one of three groups: CI; trial period of 'first BCD, then CROS'; trial period of 'first CROS, then BCD'. After these trial periods, patients opted for BCD, CROS, or No treatment. The primary outcome was speech perception in noise (directed from the front (S0N0)). Secondary outcomes were speech perception in noise with speech directed to the poor ear and noise to the better ear (SpeNbe) and vice versa (SbeNpe), sound localisation, tinnitus burden, and disease-specific quality of life (QoL). We described results at baseline (unaided situation) and 3 and 6 months after device activation. 120 patients were randomised. Seven patients did not receive the allocated intervention. The number of patients per group after allocation was: CI (n = 28), BCD (n = 25), CROS (n = 34), and No treatment (n = 26). In S0N0, the CI group performed significantly better when compared to baseline, and when compared to the other groups. In SpeNbe, there was an advantage for all treatment groups compared to baseline. However, in SbeNpe, BCD and CROS groups performed worse compared to baseline, whereas the CI group improved. Only in the CI group sound localisation improved and tinnitus burden decreased. In general, all treatment groups improved on disease-specific QoL compared to baseline. This RCT demonstrates that cochlear implantation for SSD leads to improved speech perception in noise, sound localisation, tinnitus burden, and QoL after 3 and 6 months of follow-up. For most outcome measures, CI outperformed BCD and CROS. Trial registration: Netherlands Trial Register (www.trialregister.nl): NTR4580, CINGLE-trial.